UTILIZATION OF PRIMA LIBRARIES SERVICES As A CENTER OF INFORMATION SOURCES IN SOCIAL INCLUTION PERSPECTIVE: (A Dissemination Material For Community Services At Kyai Kanjeng Sewu Islamic Boarding Scholl, Tanggul Kulon Hamlet, Tanggul Village, Wono Ayu District, Sidoarjo Regency ) - BAKHTIYAR (CV KULTURA DIGITAL MEDIA, 2022)
The purpose of the study was to describe the role of libraries in the perspective of social inclusion in active participation, to improve information literacy in rural communities as an effort to improve the welfare and quality of life of rural communities in order to welcome the era of the industrial revolution 4.0.The research object is based on the discussion of the role of libraries in the perspective of social inclusion and the urgency of information literacy in rural communities to improve welfare and quality of life in the era of the industrial revolution 4.0. The scope of the research is focused on the strategic meaning of the role of libraries based on social inclusion and digital literacy, which have a major role in improving the quality of life and welfare of rural communities. This research is called the historical approach with primary data as the primary source of information, the method of collecting data through library research, by reading various literatures on the subject of digital literacy, rural communities, social inclusion, social systems, welfare and quality of life of rural communities. The application of qualitative descriptive analysis and comparative analysis and content analysis in this study, to analyze the meaning of all concepts of digital literacy, rural communities, social inclusion and social systems. Observations are used to complement and support theory construction.The results of the study indicate that social inclusion-based libraries realize community information literacy, which plays a significant role in improving the welfare and quality of life of rural communities.